Subject and Use Index (Bulletin of the Center for Children's Books, 2024)
In the case of subject headings, the subhead "stories" refers to books for the readaloud audience; "fiction," to those books intended for independent reading. Dong Bridges: Buckley Buffalo—stories: Lindstrom Cats—stories: Sumovich Climate change—fiction: Buckley Money—stories: Michelson Monsters—fiction: Drews; Grace; Senf Murder—fiction: Cavalancia; Parker; Rose Muslim people—fiction: